Enhanced upconversion luminescence on the plasmonic architecture of Au–Ag nanocages. Issue 89 (12th September 2016) - Yin, Ze; Zhang, Xinran; Zhou, Donglei; Wang, He; Xu, Wen; Chen, Xu; Zhang, Tianxiang; Song, Hongwei
Abstract : Au–Ag nanocages with tunable surface plasmon resonance peaks were synthesized via the galvanic replacement reaction. Abstract : Au–Ag nanocages with tunable surface plasmon resonance peaks were synthesized via the galvanic replacement reaction. These tunable nanocubes with strong plasmonic effect were further fabricated into thin films composed of a random assembly of Au–Ag nanocages, which show great broadening of surface plasmon resonance absorption. After optimizing, through coupling with the excitation light, the overall upconversion luminescence intensity of NaYF4 :Yb 3+, Er 3+ on the surface of the Au–Ag nanocage film under 980 nm excitation was improved more than 15 fold.